The role of consent and uncertainty in the formation of customary international law - Niels Petersen (Max Planck Institute for Research on Collective Goods, 2011)
This contribution analyzes the role of consent in the formation of customary law. It will challenge the assumption that customary norms cannot bind states against their will. Relying on game theory, it will distinguish between different situations and argue that the role of consent differs according to the structure of the social problem that a potential norm is supposed to address. We will approach the topic in two steps. First, there will be a short review of the academic literature on the issue of consent in the formation of customary norms (1.). Second, I will propose a taxonomy of three different situations and propose individual solutions for each of these situations (2.).
Keywords: 330; Internationales Recht; Gewohnheitsrecht; Spieltheorie